2013
DOI: 10.1007/s12529-013-9336-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics of the Drug Use Disorders Identification Test (DUDIT) and the Drug Use Disorders Identification Test-Extended (DUDIT-E) Among Young Drug Users in Hungary

Abstract: The Hungarian version of DUDIT and DUDIT-E can effectively identify substance use problems among young users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
4
18
1
Order By: Relevance
“…Consistent with a previous study for Hungarian version [11], which found high correlation (r = 0.86) between the DUDIT and the DUDIT-E, the present study confirmed a good convergent validity. The strongest relationship was detected between the DUDIT and the N subscale of the DUDIT-E (r = 0.69, p < .001).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with a previous study for Hungarian version [11], which found high correlation (r = 0.86) between the DUDIT and the DUDIT-E, the present study confirmed a good convergent validity. The strongest relationship was detected between the DUDIT and the N subscale of the DUDIT-E (r = 0.69, p < .001).…”
Section: Discussionsupporting
confidence: 92%
“…model in 105 patients admitted to an inpatient substance abuse treatment unit in Northern Norway [10]. The original study conducted by Berman et al [2] implicated that the P and N factors were both made up of four components, and the T factor has three components, although these components were not supported by later studies in different languages [10,11]. In the present study, a visual inspection of the scree plot revealed two components accounting for the majority of variance for all subscales (P, N, and T sections) before the components started to level off, and two components for each subscale reached the criterion of an eigenvalue greater than one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum score for the DUDIT is 44 points, with higher scores indicating greater dependence on drugs and lower scores indicating no or minimal drug use. Researchers (Berman et al, 2003;Matuszka et al, 2014;Voluse et al, 2012) have shown the DUDIT to be a psychometrically sound measure, with high reliability and validity ( > .80).…”
Section: Methodsmentioning
confidence: 99%